Performance of Iris pseudacorus and Typha domingensis for furosemide removal in a hydroponic system. Issue 8 (2nd July 2020) - Machado, A. I.; Fragoso, R.; Dordio, A. V.; Duarte, E.
Abstract: The potential of Iris pseudacorus and Typha domingensis to remove the pharmaceutical active compound (PhAC) Furosemide from a nutrient solution was assessed. Both plants were exposed to 2 mg L −1 of furosemide during 21 days and the removal of furosemide was monitored. Vessels without furosemide were also implemented as control systems for plants development. Likewise, unplanted vessels with furosemide were employed to assess abiotic removal mechanisms. All vessels were covered with aluminum foil to avoid photodegradation of the compound. Both plants showed potential to remove Furosemide, attaining, at the end of the experiment, a removal of 42.0–66.9% and 40.5–57.8%, for Typha and Iris, respectively. The plants do not presented a visible negative stress response to the exposure to furosemide, having a positive growth rate at the end of the experiment. Biodegradation seems to play an important role in furosemide removal, being enhanced by the presence of the plants. The two macrophytes presented different removal behaviors, particularly in the first 48 h of contact time. FUR removal by Iris follows a pseudo-first order while by Typha is divide in different phases. These results indicate that different plants species seem to have different mechanisms to remove pollutants from water. Highlights: PhACs removal potential of Iris pseudacorus and Typha domingensis was assessed. Plants were exposed to 2 mg L −1 of furosemide during 21 days. Both macrophytes showed good removal efficiencies. Biodegradation of furosemide seems to be the main removal mechanism. Plants demonstrated different removal behavior along the experiment. Removal mechanisms of plants seem to differ between species.